Effect of Acioa barteri, Cassia siamea, Flemingia macrophylla and Gmelina arborea leaves on germination and early development of maize and cassava - Hauser, S. (Elsevier, 1993)
Experiments were conducted to investigate the potential allelopathic effects of Acioa barteri, Cassia siamea, Gmelina arborea and Flemingia macrophylla leaf material on the germination of maize and early growth of cassava cuttings. Incubation of maize seeds with freshly added G. arborea and C. siamea leaf material reduced germination by 35%. The effect was insignificant if leaf material was prone to microbial activity for 2 weeks before incubation of the seeds. Under non-sterile conditions, F. macrophylla and A. barteri leaf material reduced root number of maize seedlings significantly; root and shoot weight per seedling were reduced by 50%. Under sterile conditions G. arborea and C. siamea leaf material reduced germination and root number per seedling significantly at 7 days after inoculation (DAI). Root weight per germinated seed was significantly reduced at 7 DAI (P=0.25) and 13 DAI (P=0.05). F. macrophylla and A. barteri leaf material reduced root weight per germinated seedling at 13 DAI. Early development of cassava was retarded by amendments with A. barteri leaves. G. arborea leaf material retarded fungal growth. The potential benefits of this property are outweighed by the reduction of maize and cassava yields.